An investigation of behaviors influencing life satisfaction in young adult families - Snyder, Carolyn A. (Kansas State University, 2008)
Parenthood is a major life event that requires considerable lifestyle changes. As young adults become married they start a change in lifestyle that influences their health and their future children. Some couples understand that they need to change their behavior, but do not know how to do so healthfully. The poor lifestyle behaviors that produce excessive weight gain place an increased risk for premature death, heart disease, diabetes, other health problems as well as threatens their quality of life. These transitional experiences present a unique challenge that warrants exploration in the context of the young adult life stage and perceptions about health and quality of life. Currently, there is limited research of the concerns or perceptions young adults have regarding quality of life and diet related health behaviors. The purpose of this study is to identify behaviors that impact life satisfaction and health of young adult families. Two-90 minute focus groups were conducted, with pre-recruited community members 18-24 years of age. All participants were recruited from community service organizations, day care facilities and university educational classes. Participants were parents and/or married. Nutrition and Exercise majors were excluded. Both focus groups were asked seven key questions along with probing questions. All focus groups were audio taped and then transcribed verbatim. The transcriptions were coded manually by assigning a label in the margins of the transcripts for each quality of life issue that appeared. Coding allowed the data to be assembled into categories that can be used to develop quality of life and health interventions for young adults. Several issues impacting satisfaction with life and barriers to a healthy lifestyle were identified. However, money, time, family, stress, and children were primary concerns. This study identified the need to completed additional assessments to quantify the needs of young adult parents and families, so community-based partnerships can effectively develop programming and interventions.
Keywords: Young Adult Families; Quality of Life; Life Satisfaction; Health Behaviors; Focus Group; Health Sciences, Public Health (0573)